P151 V-DimERS Study - Value of D-Dimers in Estimating Risk of Significant Pulmonary Embolism and Deep Vein Thrombosis. (14th November 2013) - Molugu, C; Fisher, G; Hirons, B; Hughes, D; Raftery, S
Abstract : Hypothesis: The risk of Venous Thromboembolism (VTE) including Pulmonary Embolism (PE) increases proportionately with the level of d-dimers. Introduction: The risk of PE/VTE is low when the values of d-dimers are below the reference range (1) (<500 ng/ml in our hospital). There is no clear evidence to suggest that risk of VTE increases proportionately with rising levels of d-dimers. We studied the correlation between the various values of d-dimers and the associated risk of having a PE/VTE. Methods: Data was collected retrospectively from March 2011 to Feb 2012. For the study we divided the patients into 3 risk groups based on d-dimers. Group1: 500–1000; Group 2: 1000–5000; Group 3: >5000. Each group was analysed by separate individual. Data was collected by selecting only those patients who had definitive scan to investigate for PE/VTE Results See Table When d-dimers are >5000, the risk of PE/VTE is significantly elevated when compared to <5000. (p value <0.0005) When the d-dimers are > 5000, it's a good predictor of central PE (p value <0.0005) or Proximal DVT (p value <0.0005). Results: Conclusion: Our study suggests that when the d-dimers are significantly elevated (>5000) the associated risk of VTE (PE and DVT) is significantly elevated. The risk appears to increase proportionately until the value of 5000 beyond which it increases exponentially. Levels >5000 strongly predicts the likelihood of a central PE or a proximal DVT. Clinicians could use this as an additional indicator to thrombolyse PE's in absence of confirmatory test. Further validity studies will be required to confirm this. References: Dr Stein et Al : d-Dimer for the Exclusion of Acute Venous Thrombosis and Pulmonary Embolism; Ann Intern Med . 2004;140(8):589–602.doi:10.7326/0003–4819–140-8–200404200–00005